Parentheses matter!
x + (3/4) = x + (5/6) has no solution, since 3/4 cannot be 5/6.
However,
(x+3)/4 = (x+5)/6
6 * (x+3) = 4 * (x+5)
6x + 18 = 4x + 20
2x = 2
x =1
Done.
2007-01-19 10:37:59
·
answer #1
·
answered by Jerry P 6
·
2⤊
0⤋
x + 3/4 = x + 5/6
x - x = 5/6 -3/4
0 =! 5/6 - 3/4
This equation is undefined, as written.
If you mean (x+3)/4 = (x+5)/6...
(x+3)/4 = (x+5)/6
6(x+3) = 4(x+5) <--Cross multiplying
6x + 18 = 4x +20
6x - 4x = 20-18
2x = 2
x = 1
Check:
(1+3)/4 = (1+5)/6
4/4 = 6/6
1 = 1
2007-01-19 10:41:33
·
answer #2
·
answered by Wolfshadow 3
·
1⤊
0⤋
There is no answer that will make the equation true. Try subtracting x from both sides, and you get 3/4 = 5/6. Since that is not true, there is no value for x that will ever make it true.
2007-01-19 10:39:22
·
answer #3
·
answered by gamblin man 6
·
1⤊
0⤋
(x + 3)/4 = (x + 5)/6
Cross multiply
6(x + 3) = 4(x + 5)
6x + 18 = 4x + 20
2x = 2
x = 1
ANS : x = 1
2007-01-19 10:54:03
·
answer #4
·
answered by Sherman81 6
·
1⤊
0⤋
Cross-multiply:
4(x+5)=6(x+3)
4x+20=6x+18
Subtract 6x from both sides:
-2x+20=18
Subtract 20 from both sides:
-2x=-2
Divide -2 from both sides:
x=1
2007-01-19 10:52:20
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
x+3/4 = x+5/6
No solution because x is null. .
<>
2007-01-19 11:08:28
·
answer #6
·
answered by aeiou 7
·
1⤊
0⤋
x doesn't equal anything.
2007-01-19 10:41:31
·
answer #7
·
answered by ? 3
·
1⤊
0⤋
not possible
2007-01-19 10:38:07
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋